NIH working group report: Innovative research to improve maintenance of weight loss. (2nd December 2014) - MacLean, Paul S.; Wing, Rena R.; Davidson, Terry; Epstein, Leonard; Goodpaster, Bret; Hall, Kevin D.; Levin, Barry E.; Perri, Michael G.; Rolls, Barbara J.; Rosenbaum, Michael; Rothman, Alexander J.; Ryan, Donna
<x xml:space="preserve">Abstract</x> Objectives The National Institutes of Health, led by the National Heart, Lung, and Blood Institute, organized a working group of experts to discuss the problem of weight regain after weight loss. A number of experts in integrative physiology and behavioral psychology were convened with the goal of merging their perspectives regarding the barriers to scientific progress and the development of novel ways to improve long‐term outcomes in obesity therapeutics. The specific objectives of this working group were to: (1) identify the challenges that make maintaining a reduced weight so difficult; (2) review strategies that have been used to improve success in previous studies; and (3) recommend novel solutions that could be examined in future studies of long‐term weight control. Results Specific barriers to successful weight loss maintenance include poor adherence to behavioral regimens and physiological adaptations that promote weight regain. A better understanding of how these behavioral and physiological barriers are related, how they vary between individuals, and how they can be overcome will lead to the development of novel strategies with improved outcomes. Conclusions Greater collaboration and cross‐talk between physiological and behavioral researchers is needed to advance the science and develop better strategies for weight loss maintenance.